Aseismic ridge subduction and flat subduction: Insights from three-dimensional numerical models - Hui Zhao; Wei Leng (Earth and Planetary Physics, 2023)
Flat subduction can significantly influence the distribution of volcanism, stress state, and surface topography of the overriding plate. However, the mechanisms for inducing flat subduction remain controversial. Previous two-dimensional (2-D) numerical models and laboratory analogue models suggested that a buoyant impactor (aseismic ridge, oceanic plateau, or the like) may induce flat subduction. However, three-dimensional (3-D) systematic studies on the relationship between flat subduction and buoyant blocks are still lacking. Here, we use a 3-D numerical model to investigate the influence of the aseismic ridge, especially its width (which is difficult to consider in 2-D numerical models), on the formation of flat subduction. Our model results suggest that the aseismic ridge needs to be wide and thick enough to induce flat subduction, a condition that is difficult to satisfy on the Earth. We also find that the subduction of an aseismic ridge parallel to the trench or a double aseismic ridge normal to the trench has a similar effect on super-wide aseismic ridge subduction in terms of causing flat subduction, which can explain the flat subduction observed beneath regions such as Chile and Peru.